PREVENTIVE MEASURES FOR ARTERIAL HYPERTENSION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Among the population, the incidence of stroke diseases is in previous places, the cause of which is mainly smoking and alcohol consumption. Scientists thought much more about hypertension and its consequences. We can see that for such patients need to organize rehabilitation. The medical field is developing rapidly. In the latter years, we can observe that the disease of hypertension has been occurring more not depending on age and sex. According to research, it leads to a change in the quality of life. It is possible to restore damaged functions, with rehabilitation measures it is carried out. Timely rehabilitation can be achieved so that the disease does not escalate and the complications are reduced, and after the treatment, most patients are able to conduct their own work activities.